Representation in the European Parliament: The Role of Specialisation in Asking Parliamentary Questions. Issue 2 (3rd April 2022) - Sozzi, Fabio
ABSTRACT: Why do Members of the European Parliament (MEPs) specialise in legislative behaviour? How do MEPs use their specialisation in legislative activities? This article investigates these overlooked topics in literature and, in particular, it suggests that two factors induce specialisation in the European Parliament (EP): committee service and personal experiences. The empirical analysis centres on original dataset of 4925 parliamentary questions tabled by Italian MEPs during the sixth EP term. Results show that Italian MEPs ask more questions to Commissioner sharing the same policy portfolio and in those areas in which they have personal expertise.